Xanthohumol Blocks Proliferation and Migration of Vascular Smooth Muscle Cells in Vitro and Reduces Neointima Formation in Vivo - Liu, Rongxia (J Nat Prod, 2017)
[Image: see text] Xanthohumol (1) is a principal prenylated chalcone found in hops. The aim of this study was to examine its influence on platelet-derived growth factor (PDGF)-BB-triggered vascular smooth muscle cell (VSMC) proliferation and migration in vitro and on experimentally induced neointima formation in vivo. Quantification of resazurin conversion indicated that 1 can inhibit PDGF-BB-induced VSMC proliferation concentration-dependently (IC(50) = 3.49 μM). Furthermore, in a wound-healing assay 1 potently suppresses PDGF-BB-induced VSMC migration at 15 μM. Tested in a mouse femoral artery cuff model, 1 significantly reduces neointima formation. Taken together, we show that 1 represses PDGF-BB-induced VSMC proliferation and migration in vitro as well as neointima formation in vivo. This novel activity suggests 1 as an interesting candidate for further studies addressing a possible therapeutic application to counteract vascular proliferative disease.